Antimicrobial Activity of Acacia aulacocarpa and Acacia complanta Methanolic Extracts - Cock, I.E. (Pharmacognosy Communications)
Introduction: Australian Acacia species also had a role as traditional bush medicines for Australian Aborigines, including uses as antiseptic agents. Methods: The antimicrobial activity of methanolic extracts of Acacia aulacocarpa leaves and Acacia complanta leaves and flowers were investigated by disc diffusion assay against a panel of bacteria and fungi. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: A. aulacocarpa leaf extract inhibited the growth of 6 of the 14 bacteria tested (43%). Gram-positive and Gram-negative bacteria were both inhibited by A. aulacocarpa leaf extract. 4 of 11 Gram-negative (36%) and 2 of 3 Gram-positive bacteria (67%) had their growth inhibited by A. aulacocarpa extract. A. aulacocarpa leaf extract displayed no antifungal activity towards any of the fungi tested. The antibacterial activity of A. aulacocarpa and A. complanta leaf extracts were further investigated by growth time course assays which showed significant growth inhibition in cultures of Bacillus cereus, Aeromonas hydrophilia and Pseudomonas fluorescens within 1 h but not of Bacillus subtilis. A. complanta flower extract displayed limited antibacterial activity, inhibiting the growth of only a single bacterium (Bacillus subtilis) (7%) and displayed no antifungal activity towards any of the fungi tested. A. complanta leaf extract was unable to inhibit the growth of any of the bacteria tested but displayed antifungal activity against a nystatin resistant strain of Aspergillus niger. It did not affect Candida albicans or Saccharomyces cerevisiae growth. All extracts displayed low toxicity in the Artemia franciscana bioassay. Conclusions: The low toxicity of these Acacia extracts and their inhibitory bioactivity against bacteria validate Australian Aboriginal usage of A. aulacocarpa and A. complanta as antiseptic agents and confirms their medicinal potential.
Keywords: Acacia aulacocarpa; Acacia complanta; Australian plants; antibacterial activity; medicinal plants; toxicity